E-journal as a Student Learning Source - Nur Azmi Afifah Diens; Dinn Wahyudin; Dadi Mulyadi (Institut Agama Islam Negeri Salatiga, 2022)
In the era of the industrial revolution 4.0, information and communication technology is growing rapidly. So rapidly, almost all lines of human life use the internet, including the world of education. The presence of technology in the field of education makes learning more effective and varied and makes students more creative and innovative. One of the products of information and communication technology innovation is e-journal. This innovation develops online-based journals. This is of course very helpful and facilitates students in completing their studies. In other words, e-journals are needed as a learning resource for students. This article discusses the use of e-journals for students as a source of learning. The method of preparation in this article is a literature review. Furthermore, the final result of this article presents the concepts, types, benefits and barriers as well as the advantages and disadvantages of e-journals as a learning resource for students.